The Sympathetic Ampulla - Gauci, James; Azzopardi, Neville; Cannataci, Christine; Cortis, Kelvin; Pisani, David; Bozanic, Snezana (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Gauci J, Azzopardi N, Cannataci C, Cortis K, Pisani D, Bozanic S. The sympathetic ampulla. Turk J Gastroenterol. 2023; 34(1): 87-88.